Implantation of looped epicardial cardioverter defibrillator coil on the surface of the right ventricular outflow tract - Özyüksel, Arda; Ersoy, Cihangir; Akdeniz, Celal; Akçevin, Atıf; Türko?lu, Halil; Tuzcu, Volkan (Blackwell Publishing, 2015)
BackgroundWe present the early results of looped epicardial cardioverter defibrillator coil implantation on the anterior surface of right ventricular outflow tract in infants and children. MethodsPatients with a surgical history of an epicardial implantable cardioverter defibrillator system between 2013 and 2014 were included in the study. Patient age, gender, body weight, indications for a cardioverter defibrillator system implantation, defibrillation threshold values, and defibrillation therapies were retrospectively evaluated. ResultsThere were eight patients with a mean age of 4.42.9 years and a mean body weight of 19.5 +/- 11.7kg. Five of the patients had been diagnosed with long QT syndrome, one patient had been diagnosed with genetic channelopathy and noncompaction of the left ventricle, and two patients had been diagnosed with univentricle physiology. The implantable cardioverter defibrillator system was composed of pace-sense leads, an abdominal active can, and a defibrillation coil placed below the pulmonary valve annulus on the anterior surface of the heart. The mean defibrillation threshold was 6.6 +/- 2.3 joules. There were four appropriate therapies in two patients in a mean follow-up of 9 +/- 6.5 months. ConclusionThe significantly low defibrillation thresholds with the defibrillation coils located below the pulmonary valve annulus are encouraging. However, a larger patient series will be necessary to evaluate the safety and reliability of this technique.
WOS: 000352494400017
PubMed ID: 25683331
Keywords: Right Ventricular; Looped Epicardial; Surface